Intranasal Delivery of BACE1 siRNA and Rapamycin by Dual Targets Modified Nanoparticles for Alzheimer's Disease Therapy - Yang, Xiaotong; Yang, Wenqin; Xia, Xue; Lei, Ting; Yang, Zhihang; Jia, Wenfeng; Zhou, Yang; Cheng, Guo; Gao, Huile (Small (Weinheim an der Bergstrasse, Germany), 2022)
Alzheimer's disease (AD), as a progressive and irreversible brain disorder, remains the most universal neurodegenerative disease. No effective therapeutic methods are established yet due to the hindrance of the blood‐brain barrier (BBB) and the complex pathological condition of AD.  Therefore, a multifunctional nanocarrier (Rapa@DAK/siRNA) for AD treatment is constructed to achieve small interfering RNA of β‐site precursor protein (APP) cleaving enzyme‐1 (BACE1 siRNA) and rapamycin co‐delivery into the brain, based on Aleuria aurantia lectin (AAL) and β‐amyploid (Aβ)‐binding peptides (KLVFF) modified PEGylated dendrigraft poly‐l‐lysines (DGLs) via intranasal administration. Nasal administration provides an effective way to deliver drugs directly into the brain through the nose‐to‐brain pathway. AAL, specifically binding to L‐fucose located in the olfactory epithelium, endows Rapa@DAK/siRNA with high brain entry efficiency through intranasal administration. KLVFF peptide as an Aβ targeting ligand and aggregation inhibitor enables nanoparticles to bind with Aβ, inhibit Aβ aggregation, and reduce toxicity. Meanwhile, the release of BACE1 siRNA and rapamycin is confirmed to reduce BACE1 expression, promote autophagy, and reduce Aβ deposition. Rapa@DAK/siRNA is verified to improve the cognition of transgenic AD mice after intranasal administration. Collectively, the multifunctional nanocarrier provides an effective and potential intranasal avenue for combination therapy of AD. Aleuria aurantia lectin (AAL) and β‐amyploid (Aβ)‐binding peptides (KLVFF) modified PEGylated dendrigraft poly‐L‐lysines (DGLs) encapsulate small interfering RNA of β‐site precursor protein (APP) cleaving enzyme‐1 (BACE1 siRNA) and rapamycin for Alzheimer's disease (AD) treatment by nasal administration. Dual target modification increases about 1.4‐fold of drug accumulation in the brain. Furthermore, the combination of BACE1 siRNA, rapamycin, and KLVFF greatly improves the cognition of transgenic AD mice.